If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 23 = -2x + -7 Reorder the terms: 23 + 3x = -2x + -7 Reorder the terms: 23 + 3x = -7 + -2x Solving 23 + 3x = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 23 + 3x + 2x = -7 + -2x + 2x Combine like terms: 3x + 2x = 5x 23 + 5x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 23 + 5x = -7 + 0 23 + 5x = -7 Add '-23' to each side of the equation. 23 + -23 + 5x = -7 + -23 Combine like terms: 23 + -23 = 0 0 + 5x = -7 + -23 5x = -7 + -23 Combine like terms: -7 + -23 = -30 5x = -30 Divide each side by '5'. x = -6 Simplifying x = -6
| 3(4x+2)=10x-2 | | 14x-5=6x+1 | | 9x+1.2=-6x+7.3 | | 2tanx=7 | | -5g+2.5=18.8 | | 3g-2g+3=12 | | -2(x-5)+3=15 | | (x+5)3=36 | | 5(2l+4)=50 | | 9x^2-y^2+4=0 | | (U+5)*8=80 | | 2(a-3)=38 | | (u-6)8=24 | | 3+7t-4t+2-6= | | 0.6x+0.40(100-x)=50 | | (q-9)2=16 | | 4w^2-24w-7=0 | | (e+4)3=27 | | 3x^4=67 | | A+2b-8b= | | (Q-7)*5=25 | | -8q+18q+-13q=9 | | 2b+5j=8.43 | | 5x+101=13x-11 | | (e+5)*6=54 | | Y-5=3x-6 | | 4k^2+16k-48=0 | | 6(x+1)=2x+57 | | E+5*6=54 | | Y=.5x-150 | | -11n=-132 | | 3(2x+3)-2(4x-3)= |